Bilateral Greater Trochanteric Avulsion Fractures after Bilateral Simultaneous Total Hip Arthroplasty - Hiroaki Tagomori; Nobuhiro Kaku; Tomonori Tabata; Hiroshi Tsumura (Case Reports in Orthopedics, 2018)
We report a case of bilateral spontaneous greater trochanteric fracture after bilateral simultaneous total hip arthroplasty (THA) performed via the posterolateral approach during the early postoperative phase. A 75-year-old woman underwent bilateral simultaneous THA (BS-THA) for severe osteoarthritis with developmental dysplasia of the hip; she also presented a limited range of adduction. BS-THA was successful without any intraoperative complications. Rehabilitation with full weight-bearing exercises was initiated the day after the surgery. On the 14th postoperative day, she experienced a spontaneous left greater trochanteric fracture during a walking exercise without any trauma. Osteosynthesis was performed for the fracture on the 18th postoperative day. On the 20th postoperative day, a right spontaneous greater trochanteric avulsion fracture occurred during a transfer exercise without any trauma; this was treated on the 27th postoperative day. In the 18th postoperative month, although the right fragment showed slight upper migration, the patient had no complaints of coxalgia and both hip joints showed an excellent range of motion.